Latin American Livestock Regional Assessment Workshop - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA; CRSP, 2021)
Latin America Livestock Regional Assessment Workshop 15-18 Abr 1996 San José, Costa Rica